Die ontstaan en ontwikkeling van partypolitiek in die Oranjerivier-Kolonie, 1902-1912 - Marais, A. H; De Villiers, J.(Johannes) (Stellenbosch : Stellenbosch University, 2012)
Marais's contribution originally published as MA thesis, University of the Orange Free State.